2020
DOI: 10.1161/jaha.120.016871
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Continuous Positive Airway Pressure Treatment of Obstructive Sleep Apnea Reduces Daytime Resting Heart Rate in Prediabetes: A Randomized Controlled Study

Abstract: Background It has been widely recognized that obstructive sleep apnea (OSA) is linked to cardiovascular disease. Yet, randomized controlled studies failed to demonstrate a clear cardiovascular benefit from OSA treatment, mainly because of poor adherence to continuous positive airway pressure (CPAP). To date, no prior study has assessed the effect of CPAP treatment on daytime resting heart rate, a strong predictor of adverse cardiovascular outcomes and mortality. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Elevated daytime HR was multifactorially related and mainly determined by ODI. Similarly, a previous randomized controlled clinical study showed that patients with OSA treated with nocturnal CPAP reduced daytime resting HR and had a positive cardiovascular impact 24 . However, both anthropometric parameters and OSA severity had limited ability to predict office blood pressure.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Elevated daytime HR was multifactorially related and mainly determined by ODI. Similarly, a previous randomized controlled clinical study showed that patients with OSA treated with nocturnal CPAP reduced daytime resting HR and had a positive cardiovascular impact 24 . However, both anthropometric parameters and OSA severity had limited ability to predict office blood pressure.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a previous randomized controlled clinical study showed that patients with OSA treated with nocturnal CPAP reduced daytime resting HR and had a positive cardiovascular impact. 24 However, both anthropometric parameters and OSA severity had limited ability to predict office blood pressure. Anthropometric measurements and OSA severity predicted HRV parameters together, same as children, age remained a strong determinant.…”
Section: Discussionmentioning
confidence: 99%